Exploring HIV-Associated Neurocognitive Impairment in the Era of Effective Antiretroviral Therapy: A Primary Healthcare Perspective. (August 2022) - Munsami, Adele; Nightingale, Sam; Sorsdahl, Katherine; Joska, John A.
The prevalence of HIV-associated neurocognitive impairment (H-NCI) is concerning. Individuals on effective antiretroviral therapy (ART) may still be at risk for H-NCI as they experience longer life expectancies. There are, however, few professionals with knowledge and skills to identify H-NCI, in low- and middle-income countries. We explored qualitatively, primary healthcare workers' knowledge and views of H-NCI, in the era of effective ART, particularly their views toward task-sharing of H-NCI screening from specialists to mid-level or lay healthcare providers. The first phase of data collection involved two focus group discussions (FGDs) 23 primary healthcare workers from two facilities in the Western Cape participated in the FGDs. In the second phase of data collection12 individual, in-depth interviews were conducted in KwaZulu-Natal. Using thematic analysis, several key themes emerged. Although healthcare providers were unable to specifically identify H-NCI, they described several HIV disease and treatment related or mental health comorbidities that could be responsible for the symptoms. Despite healthcare workers reporting low frequencies of H-NCI, they favoured receiving training to screen for H-NCI with a view toward providing holistic care.